Eosinophilic folliculitis occurring after stem cell transplant for acute lymphoblastic leukemia: a case report and review. (11th July 2014) - Zitelli, Kristine; Fernandes, Neil; Adams, Brian B.
Abstract Background Eosinophilic folliculitis (EF) comprises classic eosinophilic pustular folliculitis (EPF), human immunodeficiency virus (HIV)‐related EF, and infantile EPF subtypes. A fourth proposed subtype describes EF associated with hematologic malignancy. Recently, EF has occurred after bone marrow or stem cell transplantation (SCT). Objectives We report a unique case of EF after haploidentical allogeneic SCT for acute lymphoblastic leukemia (ALL) and review the literature for similar cases. Methods A 56‐year‐old, HIV‐negative ALL patient presented with an intensely pruritic papulopustular eruption. He had undergone haploidentical allogeneic SCT 65 days earlier, which he had tolerated well. Histopathology revealed a moderately dense perifollicular and perivascular lymphocytic infiltrate with many eosinophils extending from the superficial dermis to the subcutaneous fat. Fungal stains were negative. These findings were highly consistent with EF. Results Therapy with a class II topical corticosteroid ointment, oral doxepin, and emollients achieved near‐resolution of the lesions within eight weeks. Transition to topical tacrolimus 0.1% ointment applied twice daily to residual lesions yielded complete clearance by 12 weeks with mild post‐inflammatory hyperpigmentation. The patient's ALL remains in remission. Conclusions A fourth proposed subtype of EF is associated with HIV‐negative hematologic disease. This subtype is distinguished by a predictable timeframe to presentation and a relatively rapid response to therapy. Although EF is an important consideration in all patients with hematologic malignancy, clinically heightened suspicion is warranted during the 2–3 months after transplant.